2004
DOI: 10.1116/1.1640656
|View full text |Cite
|
Sign up to set email alerts
|

Secondary defect formation in bonded silicon-on-insulator after boron implantation

Abstract: Silicon-on-insulator (SOI) has proven to be a viable alternative to traditional bulk silicon for fabrication of complementary metal–oxide–semiconductor devices. However, a number of unusual phenomena with regards to diffusion and segregation of dopants in SOI have yet to be explained. In the present study, SOITEC wafers were thinned to 700 and 1600 Å using oxidation and etching. Ion implantation was performed into SOI and bulk silicon wafers using B+11 ions at 6.5 and 19 keV with a dose of 3×1014 cm−2. Thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The possible effect of the Si top layer/BOX interface acting as a sink, for example, has been confirmed by some already published experimental analysis [2,5], and ruled out by others [3,7].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The possible effect of the Si top layer/BOX interface acting as a sink, for example, has been confirmed by some already published experimental analysis [2,5], and ruled out by others [3,7].…”
Section: Introductionmentioning
confidence: 57%
“…It is commonly accepted [2,3,[5][6][7] that the density and size of EOR defects decreases when passing from Bulk Silicon to SOI but different arguments are used in the literature to explain this reduction. The possible effect of the Si top layer/BOX interface acting as a sink, for example, has been confirmed by some already published experimental analysis [2,5], and ruled out by others [3,7].…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that the dopants behavior and extended defects formation depend on the top Si film thickness in SOI [11][12][13] , but up to now, a deep understanding about the mechanism of atomic transport and dopant activation in SOI substrates lacks. In this work, we discuss silicon crystal structural characteristics and electrical activation of As implanted in SOI layers with different thicknesses, considering the amorphization depth reached by dopant implantation and the crystal recovery process via thermal treatment, whether it returns to single crystal structure or becomes poly-crystalline.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the dopants' behaviour and extended defects formation depend on the top Si film thickness in SOI [11][12][13]. Until now, there has been a lack of deep understanding about the mechanism of atomic transport and dopant activation in SOI substrates.…”
Section: Introductionmentioning
confidence: 99%